Satisfaction of MERSI EMR Users in the Emergency Department of Cengkareng Regional Hospital Through the End User Computing Satisfaction (EUCS) Approach - Ahmad Bukhori; Dina Sonia; Bangga Agung Satrya; Muhammad Fuad Iqbal (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of an Electronic Medical Record (EMR) system in the Emergency Department (ED) is a crucial aspect in supporting rapid response to patient care. In emergency situations, the speed and accuracy of information are vital, necessitating research to measure user satisfaction with the MERSI EMR system. This evaluation aims not only to assess user satisfaction but also to identify system weaknesses to improve efficiency, responsiveness, and effectiveness in supporting services in the ED. This study aims to determine user satisfaction with the MERSI system at the ED of RSUD Cengkareng using the End User Computing Satisfaction (EUCS) approach. A quantitative descriptive method was used with a quota sampling technique. The population consisted of 51 medical personnel operating the MERSI system in the ED. The results showed that for the Content variable, 88.2% of respondents were satisfied and 11.8% were not. For Accuracy, 80.4% were satisfied and 19.6% were not. For Format, 88.2% were satisfied and 11.8% were not. For Timeliness, 82.4% were satisfied and 17.6% were not. Meanwhile, for Ease of Use, 64.7% were satisfied and 35.3% were not. These findings indicate that the overall operation of MERSI has met user expectations, particularly in terms of information relevance, data accuracy, and interface design. The study recommends integrating MERSI with the hospital information system (SIMRS) as a backup effort to enhance the efficiency and reliability of healthcare services in the ED. Additionally, integration with a bridging system similar to BPJS PCare is expected to enable online access to patient medical records. Training for medical personnel should also be improved to optimize the use of the EMR system.